URBAN ECOLOGY: HOUSE RAT (RATTUS RATTUS) MANAGEMENT AND BEE (TRIGONA SP.) KEEPING IN RW IX GRIYA BHAYANGKARA, SUKODONO - Mahendra Kusuma, Ramadhani; Sasongko, Purnomo Edi; Mindari, Wanti; Wijayanti, Fitri; Lestari Tarigan, Puji; Nur Supriyadi, Yudi; Windriyanti, Wiwin; Kresna Setiadi, Iwan (Batara Wisnu : Indonesian Journal of Community Services, 2025)
Urban environments often grapple with the dual challenges of pest management and sustainable practices, highlighting a crucial research gap in integrating effective and eco-friendly solutions. This activity addresses the issue of house rat (Rattus rattus) infestations and the potential for Trigona bee (Trigona sp.) keeping in RW IX Griya Bhayangkara, Sukodono. The primary objective was to develop and implement a training program for constructing environmentally friendly rat traps and establishing Trigona bee colonies. Utilizing a hands-on approach, the methodology included the design of simple, water gallons-based rat traps and the setup of bee bamboo-hives tailored for urban settings. The expected outcome where the introduction of simple rat traps could reduce house-rat populations, while Trigona beekeeping offered additional economic benefits and environmental sustainability. This activity underscores the importance of community engagement in adopting these methods, demonstrating that local resource utilization and practical training can effectively address urban ecological challenges. The implications of this activities extend to enhancing urban pest management strategies and promoting sustainable urban agriculture practices, contributing to overall community well-being, ecological resilience, and the achievement of SDGs.